2015
DOI: 10.1128/jvi.02565-14
|View full text |Cite
|
Sign up to set email alerts
|

JC Virus Quasispecies Analysis Reveals a Complex Viral Population Underlying Progressive Multifocal Leukoencephalopathy and Supports Viral Dissemination via the Hematogenous Route

Abstract: For the first time, the JC polyomavirus population contained in different body compartments of patients diagnosed with progressive multifocal encephalopathy has been studied by deep sequencing. Two main findings came out of this work. First, it became apparent that the complexity of the viral population associated with PML has been highly underestimated so far, suggestive of a highly dynamic process of reorganization of the noncoding control region of JC polyomavirus in vivo, mainly in CSF and blood. Second, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
40
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 36 publications
7
40
1
Order By: Relevance
“…JCV quasispecies have been reported in the regulatory region and in VP1 from urine samples using deep sequenc- ing (36,37). NGS analysis revealed that the JC viral population is often a complex mixture composed of multiple viral variants that contribute to the quasispecies in the cerebrospinal fluid (CSF) of PML patients (37). As far as we are aware, finding JCV quasispecies with a mutated TAg in the brain of patients with PML has not been reported previously.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…JCV quasispecies have been reported in the regulatory region and in VP1 from urine samples using deep sequenc- ing (36,37). NGS analysis revealed that the JC viral population is often a complex mixture composed of multiple viral variants that contribute to the quasispecies in the cerebrospinal fluid (CSF) of PML patients (37). As far as we are aware, finding JCV quasispecies with a mutated TAg in the brain of patients with PML has not been reported previously.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the presence of quasispecies in the regulatory region of BKV has also been reported, with some of the quasispecies being associated with virus replication (35). JCV quasispecies have been reported in the regulatory region and in VP1 from urine samples using deep sequenc- ing (36,37). NGS analysis revealed that the JC viral population is often a complex mixture composed of multiple viral variants that contribute to the quasispecies in the cerebrospinal fluid (CSF) of PML patients (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, when immunosuppression is not readily reduced to permit specific T cells to resume control over BKPyV replication (14-17), viral variants with rearranged NCCRs (rr-NCCRs) emerge that are associated with higher plasma viral loads and more severe renal allograft pathology (8). Similar rr-NCCRs of JC polyomavirus have been linked with the emergence of progressive multifocal leukoencephalopathy, a debilitating, often fatal brain disease in immunocompromised patients with HIV/AIDS or receiving transplantation or therapies for cancer and immune diseases (18)(19)(20)(21)(22). The archetype NCCR of polyomaviruses is approximately 400 bp in length and harbors the origin of replication as well as bidirectional promoter/ enhancer functions that, in concert with the host cell signals, control the timing and sequential activation of early viral gene region (EVGR) expression, viral DNA genome replication, and late viral gene region (LVGR) expression.…”
mentioning
confidence: 99%
“…The answer is at present not resolved, but it seems to favor the concept of a progression within an individual. One reason is that whereas multiple genotypes of the JCV NCCR are associated with PML, only a single version of the archetype is usually found in the urine of an infected individual [4,5]. This genetic drift could only occur so quickly if a form of the mutated archetype is highly adaptable, versus the archetype, to a particular cell type en route from distal sites to the brain.…”
Section: Descriptionmentioning
confidence: 99%